2018
DOI: 10.1111/vop.12548
|View full text |Cite
|
Sign up to set email alerts
|

The retina of the collared peccary (Pecari tajacu): structure and function

Abstract: To the best of our knowledge, this study describes the collared peccary's retinal features for the first time. A comparison of our findings with data from other ungulate species shows some similarities between the peccary and pig retinas. Further studies are warranted to determine whether the peccary can be used alongside the pig as an animal model in retinal studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 28 publications
(50 reference statements)
0
2
0
Order By: Relevance
“…The peccary's retina had a typical vascular pattern called holangiotic as early described [39], the optic disc (OD) has an oval appearance. It is located just below the center of the retina and temporally displaced (Fig 1).…”
Section: Gross Anatomy Retinal Area and Identification Of Ganglion Cmentioning
confidence: 98%
See 1 more Smart Citation
“…The peccary's retina had a typical vascular pattern called holangiotic as early described [39], the optic disc (OD) has an oval appearance. It is located just below the center of the retina and temporally displaced (Fig 1).…”
Section: Gross Anatomy Retinal Area and Identification Of Ganglion Cmentioning
confidence: 98%
“…Recently, Ezra-Alia et al, have reported more detailed aspects of the peccary retina. They showed that the amount of M/L cones is greater than S cones, and that the amplitude of the combined response of cones and rods is smaller compared to domestic pigs, but very similar to minipigs [39].…”
Section: Introductionmentioning
confidence: 99%